2011
DOI: 10.1371/journal.pone.0022239
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Accumbens Injection of a Dopamine Aptamer Abates MK-801-Induced Cognitive Dysfunction in a Model of Schizophrenia

Abstract: Systemic administration of the noncompetitive NMDA-receptor antagonist, MK-801, has been proposed to model cognitive deficits similar to those seen in patients with schizophrenia. The present work investigated the ability of a dopamine-binding DNA aptamer to regulate these MK-801-induced cognitive deficits when injected into the nucleus accumbens. Rats were trained to bar press for chocolate pellet rewards then randomly assigned to receive an intra-accumbens injection of a DNA aptamer (200 nM; n = 7), tris buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 45 publications
(54 reference statements)
4
30
0
Order By: Relevance
“…The next night, we gave mice 3g of milk chocolate (Hershey's, Hershey, PA) at dark onset and recorded sleep-wake behavior and wheel running over the next 12 hours (19:00-7:00). We chose to use chocolate because it is used as a reward in rodent operant studies (Holahan et al, 2011, King et al, 2011), and cataplexy in mice and dogs is increased by palatable foods (Siegel et al, 1986, Clark et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…The next night, we gave mice 3g of milk chocolate (Hershey's, Hershey, PA) at dark onset and recorded sleep-wake behavior and wheel running over the next 12 hours (19:00-7:00). We chose to use chocolate because it is used as a reward in rodent operant studies (Holahan et al, 2011, King et al, 2011), and cataplexy in mice and dogs is increased by palatable foods (Siegel et al, 1986, Clark et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…In this model, treatment with D1-or D2-like receptor antagonists reversed MK-801-associated behavior, thus it was concluded that perseveration may be a result of overactivity of DA in the nucleus accumbens [38]. The potential for a DAbinding DNA aptamer to offer an alternative to traditional D1-and D2-like receptor antagonists was therefore explored [30,39]. The authors postulated that the aptamer would bind excess DA and prevent the molecules from binding to DA receptors, thereby normalizing lever pressing behavior.…”
Section: Neurotransmitters and Neurotoxinsmentioning
confidence: 99%
“…Number in parentheses = rats per group. Figure reproduced from Holahan et al, 2011, in accordance with the PLOS Creative Commons Attribution (CC BY) license[39].…”
mentioning
confidence: 98%
“…the dopamine aptamer investigated here). 35,36,48,49 These difficulties have been attributed to the complexity in targeting molecules with low molecular mass and rotatable bonds. 59,60 Recent advances in solution-phase SELEX methods that obviate tethering targets have enabled identification of aptamers that recognize small-molecule, low-epitope targets.…”
Section: Resultsmentioning
confidence: 99%